The Shame and the Sorrow : Dutch-Amerindian Encounters in New Netherland - Merwick, Donna (Early American series., 2006)
How are the Dutch to be judged? Donna Merwick, in The Shame and the Sorrow, asks this question. She points to a betrayal both of their own values and of the native peoples. She also directs us to the self-delusion of hegemonic control. Her work belongs alongside the best of today's postcolonial studies in the description of cross-cultural violence and subtle questioning of the nature of writing its history."--Book jacket.